Advokasi Penerapan Kawasan Tanpa Rokok di Sekolah - Ulfa, Annisa Sayyidatul; Damayanti, Rita (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2021)
Background. Passive smokers in Indonesia reaches 75% or 96.9 million people. 66.2% students are exposed to cigarette in closed public spaces. Ministry of Education and Culture issued Permendikbud 64/2015 concerning KTR in the School Environment. implementation of KTR in schools still need optimization. Objective to see how the role of students in the advocacy process in implementing schools as smoke-free areas. Method. This research is a qualitative descriptive research with case study design conducted in a Junior High School of Bogor Regency. There were 7 informants. The data collection technique used Focus Group Discussion (FGD) and in-depth interviews by looking at the advocacy process using the "A" Advocacy Framework. Results. Students act as implementers of KTR in schools by advocating teachers to become student facilitators, school leaders as policy makers, and shop traders around the school. Students identify perceived problems, formulate strategies, analyze targets and conduct advocacy. The agreement formed include implementation of KTR according to the school’s ability and condition, installing KTR signs, applying KTR task-force and advocating stalls around schools to put down cigarette advertising banners Conclusion. Students can become agents of change for the implementation of KTR in schools with facilitation and support from teachers and principals.